Factors Associated With Attendance at a 1-yr Post–Cardiac Rehabilitation Risk Factor Check. Issue 3 (May 2020) - Giannoccaro, Justin D.; Aggarwal, Sandeep; Grace, Sherry L.; Campbell, Tavis S.; Hauer, Trina; Arena, Ross; Rouleau, Codie R.
Abstract : Purpose: Patients with coronary artery disease (CAD) often fail to maintain secondary prevention gains after completing cardiac rehabilitation (CR). Follow-up appointments aimed at assessing cardiac status and encouraging maintenance of health behaviors after CR completion are generally offered but not well-attended. This study explored patient characteristics and barriers associated with nonattendance at a 1-yr follow-up visit following CR completion. Methods: Forty-five patients with CAD who completed a 12-wk outpatient CR program but did not attend the 1-yr follow-up appointment were included. Participants responded to a survey consisting of open-ended questions about follow-up attendance, a modified version of the Cardiac Rehabilitation Barriers Scale, and self-report items regarding current health practices and perceived strength of recommendation to attend. Thematic analysis was used to derive categories from open-ended questionnaire responses. Linear regression was used to assess characteristics associated with appointment attendance barriers. Results: Barrier themes were as follows: (1) lack of awareness; (2) perception of appointment as unnecessary; (3) practical or scheduling issues; (4) comorbid health issues; and (5) anticipated an unpleasant experience at the appointment. Greater self-reported barriers (mean ± SD = 1.97/5.00 ± 0.57) were significantly associated with lower perceived strength of recommendation to attend the follow-up appointment (2.82/5.00 ± 1.45), P = .005. Conclusions: Providing a stronger recommendation to attend, enhancing patient awareness, highlighting potential benefits, and supporting self-efficacy might increase 1-yr follow-up appointment attendance and, in turn, support long-term adherence to cardiovascular risk reduction behaviors. Abstract : Supplemental Digital Content is Available in the Text.This study examined barriers to attending a follow-up visit 1 yr after cardiac rehabilitation to support maintained risk reduction among 45 patients. Qualitative analysis indicated that awareness, perceived necessity, scheduling/health issues, and anticipated experiences were important patient considerations. Barriers were greater in those who perceived less provider encouragement to attend.